Hydrogen peroxide decomposition into oxygen in different soils: Kinetic analysis, mechanism and implication in catalyzed hydrogen peroxide propagations. (1st July 2021) - Vafaei Molamahmood, Hamed; Qin, Jiaolong; Yu, Shiqin; Long, Mingce
Abstract: Rapid hydrogen peroxide (H2 O2 ) decomposition in soils is one of the most important barriers standing in front of catalyzed H2 O2 propagations (CHP) for soil and groundwater remediation, and the rates depend greatly on soil components. However, there are lack of indicators to quantitatively evaluate the processes in various soils. Different from previous studies focusing on H2 O2 decomposition, O2 production kinetics are more valuable due to the direct relationship with H2 O2 utilization. In this contribution, O2 production during H2 O2 decomposition in the soil slurry was in situ detected using a fiber-optic oxygen transmitter. A kinetic model of O2 production was developed, which can be fitted well by the measured data of 18 soil samples. A kinetic constant on O2 production ( k O2 ) ranging from 0.001 min −1 to 0.057 min −1 was obtained from the model, which represents the diverse catalytic activity of the soils. The constant k O2 is correlated with the contents of manganese, iron as well as inorganic carbon in the soils, and Mn mineral is the dominant factor. Three types of soils were selected to investigate the effect of acid-washing and stabilizer phosphate addition on phenol oxidation in CHP. Acid-washing can greatly suppress O2 production, while phosphate addition is not desirable for the highly active soils. Phenol slightly inhibits O2 production in the soils with higher k O2 values, which are inverse with those of phenol degradation. Acid-washing can remove Mn minerals but retain most of Fe components, and accordingly increase phenol degradation. Both hydroxyl radicals and superoxide radicals contribute to phenol degradation, and the latter ones display a more significant role. This work increases the understanding of the mechanism of H2 O2 decomposition in the soils and provides a parameter ( k O2 ) to guide CHP technologies in soil remediation. Graphical abstract: Image 1 Highlights: Rapid H2 O2 decomposition in soils is a challenge in catalyzed H2 O2 propagations. A kinetic model of O2 production is developed based on in-situ detection of oxygen. The obtained constants ( k O2 ) for 18 soils represent soil activities for H2 O2 decay. Mn contents in the soils are the dominant factors in H2 O2 disproportion in soils. Acid-washing can remove Mn minerals, decrease k O2 and promote oxidation in soils.